Three dimensional multiscalar neurovascular nephron connectivity map of the human kidney across the lifespan - Liam McLaughlin; Bo Zhang; Siddharth Sharma; Amanda L. Knoten; Madhurima Kaushal; Jeffrey M. Purkerson; Heidie L. Huyck; Gloria S. Pryhuber; Joseph P. Gaut; Sanjay Jain (Nature Communications)
Abstract The human kidney maintains homeostasis through a complex network of up to a million nephrons, its fundamental tissue units. Using innovative tissue processing and light sheet fluorescence microscopy, we mapped the 3D neurovascular connectivity of nephrons to understand how their structural organization enables coordinated functions like filtration, absorption, and blood pressure regulation. Our analysis revealed developmental changes in glomerular orientation, density, volume, and innervation from birth through aging. We discovered an extensive nerve network connecting different nephron segments and organizing glomeruli into distinct communities. These communities are linked through “mother glomeruli” that serve as control centers, creating a repeating pattern throughout the cortex. This sophisticated neural organization, which is underdeveloped in newborn kidneys and disrupted in conditions like diabetes and hydronephrosis, appears to facilitate synchronized responses to maintain fluid balance. The findings provide insights into how the kidney’s structural architecture enables coordinated function across its numerous nephrons.